PENGARUH PENDIDIKAN TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI KELURAHAN LAING KECAMATAN TANJUNG HARAPAN KOTA SOLOK - Dian Rizke; Patrisia Juwita (Jurnal Public Administration, Business and Rural Development Planning, 2019)
Tanjung Harapan sub-district is one of the two sub-districts in the city of Solok. Judging from the existing village standards in the city of Solok, the level of community education in the Laing sub-district of Tanjung Harapan sub-district is still low, where many school-age residents attend school and their average education level is middle level. Based on the results of observations in the field, that the level of community participation in the village of Laing, Tanjung Harapan sub-district, the city of Solok on rural / urban development is not optimal, one of which is caused by the factor of community education levels that are still relatively low The success of the implementation of government programs in the framework of national development is very dependent on the participation of all levels of society. Community involvement is very important in the success of programs owned by the government. The community has a large potential of resources and if local governments are able to generate and manage them, many activities can be carried out without much involvement from the government. The government only needs to stimulate the community and subsequently the community themselves work hand in hand to solve it. However, this can be achieved if the human resources possessed have the quality, so they are able to compete and answer all development challenges.